2016
DOI: 10.1002/smr.1805
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting spatial code proximity and order for improved source code retrieval for bug localization

Abstract: Practically all information retrieval based approaches developed to date for automatic bug localization are based on the bag‐of‐words assumption that ignores any positional and ordering relationships between the terms in a query. In this paper, we argue that bug reports are ill‐served by this assumption because such reports frequently contain various types of structural information whose terms must obey certain positional and ordering constraints. It therefore stands to reason that the quality of retrieval for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…Prior work has shown that MRF's positional proximity significantly outperforms DLM's simplified model for the problem of bug localization applied at the file level [12]. From this initial study, we see that the problem of feature location at the method level does not show the same consistent improvement from positional proximity as bug localization.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Prior work has shown that MRF's positional proximity significantly outperforms DLM's simplified model for the problem of bug localization applied at the file level [12]. From this initial study, we see that the problem of feature location at the method level does not show the same consistent improvement from positional proximity as bug localization.…”
Section: Discussionmentioning
confidence: 73%
“…Note that the model constant λ F I has no impact on the rankings with the FI assumption. However, we use this parameter in SD model together with λ SD to combine the scores obtained with the 2-node cliques and the 3-node cliques by enforcing λ F I +λ SD = 1 [12].…”
Section: A Markov Random Fields (Mrf)mentioning
confidence: 99%
See 2 more Smart Citations
“…Probabilistic models for natural language can also be used to analyze computer languages or computer code [97]. As an example, in the paper "Mining concepts from code with probabilistic topic models" the authors analyze large-scale code repositories with the aim of increased understanding of software code structure and functionality, while also enabling increased code reuse and code refactoring [66].…”
Section: Applicationsmentioning
confidence: 99%